Determining the efficiency of using egg products for the stabilization of emulsion when making milk-containing curdsbased products - Belemets, Tatiana; Radzievska, Irina; Yushchenko (Gonchar), Natalia; Bandura (Kuzmyk), Uliana (My University, 2020)
The appropriateness of using the phospholipids of egg products has been considered as an alternative to synthetic emulsifiers in the technology of making milk-containing curds-based sour milk products (hereinafter, milk-containing products) of the functional purpose. Underlying the development is the improvement of conventional technology by replacing 50 % of milk fat with a blend of natural vegetable oils (based on the mathematically calculated ratios). This could increase the content of essential fatty acids to the level commensurate with the physiological norms of their consumption. Adding the products of chicken egg processing as a useful and safe natural emulsifier would prevent the separation of the product's fatty phases. The emulsifying mixture "Prottekt 01" has been used as control. The rational dosage for introducing the selected natural emulsifiers has been determined, based on the calculation of 1...4 % to the mass of the introduced vegetable fats (blend), which ensure the highest fat-retaining capacity (FRC) indicator and do not affect the organoleptic characteristics of the product. It has been established that the stability of direct emulsifiers (DE) «o/w» is 100 % in the case of using egg yolk powder or the emulsifier "Prottekt 01" in the amount of 3 %; egg powder or albumin – 4 %. The rational ratio of the formulation components has been determined for such emulsions – water phase:vegetable oil blend:egg yolk powder – as 21:76:3, provided the lowest possible percentage of a water phase (whey) is introduced. The dependence of a moisture-retaining capacity indicator on the moisture content in a milk-containing product that included the experimental samples of emulsions has been confirmed. The dependence established is in good agreement with a phenomenon of the reduced moisture-retaining capacity in a food product when its fat content increases as a result of the lower moisture-retaining capacity of the fatty phase compared with the protein phase. The derived dependence of lecithin content on the indicators of FRC and DE proves the appropriateness of choosing the egg yolk powder as an emulsifier for making a milk-containing curds-based sour milk product. The highest indicators of FRC, 5 cm3/g, and the formation of 100 % of DE, are observed when using 3 % of the egg yolk powder (with a lecithin content of 10.3 g/100 g of the product) in the emulsifier composition
Keywords: blend of vegetable oils; суміш рослинних олій; milk-containing curdsbased sour milk product; кисломолочний продукт, що містить молоко; egg yolk powder; яєчний жовток в порошку; кафедра технології молока і молочних продуктів